2011
DOI: 10.1007/s10792-011-9484-2
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence and optical coherence tomography findings in optic disc pit-associated maculopathy: case series

Abstract: The aim of this case series was to report and discuss the clinical, fundus autofluorescence (FAF), and optical coherence tomography (OCT) findings of four eyes of three cases with optic disc pit (ODP)-related serous macular detachment. Three cases were referred to the retina department of our hospital for decreased visual acuities in four of their eyes. In addition to ophthalmological examinations, OCT and FAF were also performed. ODP-related serous macular detachment was detected clinically in all the eyes. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Contrary to Lincoff et al’s findings, 17 outer retinal dehiscence may not be a mandatory step for the occurrence of subretinal fluid accumulation. Most of the earlier studies describing features of ODP-M with TD-OCT do not report the presence of an outer retinal dehiscence, 5 , 15 19 with few exceptions. 6 , 20 A recent study by Imamura et al utilized OCT to characterize ODP-M in a consecutive series of 16 patients and found outer retinal dehiscence in only 27% of eyes and presence of subretinal fluid in some patients without outer retinal holes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Contrary to Lincoff et al’s findings, 17 outer retinal dehiscence may not be a mandatory step for the occurrence of subretinal fluid accumulation. Most of the earlier studies describing features of ODP-M with TD-OCT do not report the presence of an outer retinal dehiscence, 5 , 15 19 with few exceptions. 6 , 20 A recent study by Imamura et al utilized OCT to characterize ODP-M in a consecutive series of 16 patients and found outer retinal dehiscence in only 27% of eyes and presence of subretinal fluid in some patients without outer retinal holes.…”
Section: Discussionmentioning
confidence: 93%
“…Postel et al 13 proposed that a rhegmatogenous mechanism might be the triggering event by which liquefied vitreous enters the optic disk pit via a small hole in the overlying diaphanous tissue. 14 Lincoff et al 15 suggested a sequence of events in the natural history of ODP-M, beginning with fluid accumulation in various retinal layers, with subsequent development of outer retinal dehiscence and movement of fluid through the dehiscence into the subretinal space. 14 …”
Section: Discussionmentioning
confidence: 99%
“…15,22 In contrast, classic ODP/ODP is believed to be the result of incomplete closure of the superior end of the embryonic fissure, which seems not to be suitable for explaining our case either. 3,23,24 Preoperatively, we had completely normal retinal and optic nerve structures as documented by OCT, therefore completely eliminating the possibility of an inborn pathology. To further test whether there is a genetic factor involved in our case, we performed whole-exome sequencing on this patient and her core family.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] FAF is known to be helpful in the diagnosis of diseases in which lipofuscin and other fluorophores accumulate in RPE cells. [5][6][7] Studies are also available that suggest FAF might be used in the diagnosis of macular edema. 9,14,15 McBain et al evaluated 34 patients who developed ME and determined that, when compared with FAF, FA has an 81% sensitivity and a 69% speci-ficity.…”
Section: Discussionmentioning
confidence: 99%
“…4 Fundus autofluorescence (FAF) imaging is a novel imaging technique that can be used, along with other diagnostic tools, to track various retinal pathologies. [5][6][7] FAF is derived mainly from lipofuscin, a waste byproduct of phagocytosed photoreceptor outer segments, which accumulate in the retinal pigment epithelium (RPE) and autofluoresces between 500 and 750 nm (the peak emission is at 630 nm). 8 FAF is a rapid, noninvasive imaging method with 69% specificity and 81% sensitivity for cystoid macular edema (ME).…”
mentioning
confidence: 99%